Productivity of sweet cherry in southern Ukraine under stress conditions - Bondarenko, P.; Yudytska, Iryna (Харків : 2022, 2022)
Sweet cherry is one of the most important stone fruit crops in Ukraine, with production level of 60-85 thousand t annually, with most of the industrial production concentrated in the Steppe zone [1]. The question of optimal cherry rootstock for intensive orchards is still very open, and the tendency of climate change observed throughout the world makes it more pressing nowadays. According to the meteorological data, in recent years, mean daily air temperature and sum of active temperatures in Melitopol increased compared to mean long-term values, while hydrothermal coefficient and air humidity decreased, more spring frosts in April-May are observed, and precipitation distribution shifted to heavy rains followed by prolonged periods of draught [2]. Thus, cherry rootstocks should be adaptive to a wide range of possible abiotic stress factors. The aim of our research was to assess the main production indices of sweet cherry trees grafted on different clonal rootstocks
Bondarenko P., Yudytska I. Productivity of sweet cherry in southern Ukraine under stress conditions. Scientific basis to raise agricultural production effectiveness : Materials of the VІ International scientific and practical conference, Kharkiv, 29-30th of November 2022. – Kharkiv : State Biotechnological University, 2022. – P. 22-24.
Keywords: cherry; Melitopolska chorna; cultivars; trees grafted